2019
DOI: 10.3390/cancers11060816
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Histiocytoid Cells and Multinucleated Giant Cells in Fine-Needle Aspiration Cytology of the Thyroid Predict Lymph Node Metastasis of Papillary Thyroid Carcinoma

Abstract: Preoperative detection of cervical lymph node metastasis in papillary thyroid carcinoma (PTC) is crucial for determining the surgical strategy to prevent locoregional recurrence of the disease. We identified the cytological predictors of lymph node metastasis in 222 consecutive patients with PTC using fine-needle aspiration cytology (FNAC) of the thyroid. Cervical lymph node metastases occurred in 99 (44.6%) of 222 PTC patients. Lymph node metastasis was significantly associated with tumor multifocality (p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Except that, we noticed that cases which had the presence of MGC, numerous nuclei and high N/C ratio in it, tended to be larger in tumor size, had more lymph node involvement and extrathyroidal extension. Our results were close to the two previous studies 8,15 . We have presumed that if there were more cases with resection material, it would have a statistically positive effect on our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Except that, we noticed that cases which had the presence of MGC, numerous nuclei and high N/C ratio in it, tended to be larger in tumor size, had more lymph node involvement and extrathyroidal extension. Our results were close to the two previous studies 8,15 . We have presumed that if there were more cases with resection material, it would have a statistically positive effect on our results.…”
Section: Discussionsupporting
confidence: 90%
“…Our results were close to the two previous studies. 8,15 We have presumed that if there were more cases with resection material, it would have a statistically positive effect on our results. In cases which there is no doubt about the diagnosis of malignancy, it is highly possible to use the presence of MGC as an important data of prognostic value.…”
Section: Discussionmentioning
confidence: 89%
“…However, PTC is prone to metastasize to cervical lymph nodes, especially the central ones. Thus, a proportion of patients with PTC present unfavorable prognosis possibly because 20%-90% of PTC cases present with cervical lymph node metastasis (LNM) [5,6]. Moreover, cervical LNM is the main risk factor associated with high recurrence in patients with PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Multinucleated giant cells are found in various thyroid lesions including Hashimoto’s thyroiditis, granulomatous thyroiditis, palpation thyroiditis, and PTC [ 29 ]. Some studies have reported that multinucleated giant cells are rarely found in NIFTP and follicular adenoma [ 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%